2013
DOI: 10.1177/073953291303400104
|View full text |Cite
|
Sign up to set email alerts
|

Database Search Results Can Differ from Newspaper Microfilm

Abstract: The results of this study should raise some concerns for researchers who assume that a database always accurately reflects the print edition of The New York Times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Most articles (83.5%) used a single database, but those articles that used more than one database often used Nexis Uni and LexisNexis products with ProQuest (Buntain et al, 2023). Both this study and Youngblood, et al (2013) found LexisNexis Academic/Nexis Uni to be the most popular resource amongst communication and journalism scholars' news analyses.…”
Section: Sampling With Subscription News Aggregator Databasesmentioning
confidence: 63%
See 2 more Smart Citations
“…Most articles (83.5%) used a single database, but those articles that used more than one database often used Nexis Uni and LexisNexis products with ProQuest (Buntain et al, 2023). Both this study and Youngblood, et al (2013) found LexisNexis Academic/Nexis Uni to be the most popular resource amongst communication and journalism scholars' news analyses.…”
Section: Sampling With Subscription News Aggregator Databasesmentioning
confidence: 63%
“…Sampling involves developing a subset of content that is representative of the population, helping researchers economize their efforts (Krippendorff, 2004, p. 84). Prior research shows that U.S. scholars of the mass communication and journalism disciplines tend to develop their samples with content from major print legacy news outlets, newspapers that originated in print, like The New York Times, The Washington Post, or USA Today (Riffe & Freitag, 1997;Youngblood et al, 2013). A study of dissertations and theses that used newspapers in the research found that the majority (67%) used only newspapers from the U.S., 23% used non-U.S. newspapers, and about 10% used both (Feeney, 2014).…”
Section: Sampling With Subscription News Aggregator Databasesmentioning
confidence: 99%
See 1 more Smart Citation
“…3 There is a small but important body of literature that examines the databases themselves. This includes research that analyzes the similarities in news stories among databases (Weaver and Bimber 2008); the overlap in stories from the same news sources between databases and physical print (Ridout, Fowler, and Searles 2012); and the overlap in content availability between databases and microfilm (Youngblood, Bishop, and Worthington 2013). Existing work, however, has not examined how databases change over time or how those changes affect the discipline.…”
Section: What Are News Databases and What Is Changing?mentioning
confidence: 99%
“…Loss of information is of particular interest to communication scholars who use full-text databases, created by aggregators such as Lexis-Nexis Academic or EBSCOhost, to acquire material for content analysis. Youngblood et al 8 write that media researchers assume-incorrectly-that the database version of a newspaper is identical to the print version. They argue that the mismatch has substantial implications for content analysis.…”
Section: Literature In Adjacent Fieldsmentioning
confidence: 99%